2016
DOI: 10.1021/acs.est.5b03418
|View full text |Cite
|
Sign up to set email alerts
|

Robust Thermoresponsive Polymer Composite Membrane with Switchable Superhydrophilicity and Superhydrophobicity for Efficient Oil–Water Separation

Abstract: Herein, we report for the first time on the fabrication of a robust, thermoresponsive polymer membrane produced by the combination of an elastic polyurethane (TPU) microfiber web and poly(N-isopropylacrylamide) (PNIPAM). PNIPAM hydrogel is evenly coated on the surface of TPU microfibers, and thus, the wettability of TPU-PNIPAM membrane is amplified by taking advantage of the hierarchical structure and increased surface roughness. The TPU-PNIPAM membrane possesses switchable superhydrophilicity and superhydroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
125
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(130 citation statements)
references
References 41 publications
0
125
0
1
Order By: Relevance
“…With advantages of low cost and high e±ciency, centrifugal spinning technology has been developed from the initial preparing arti¯cial hair to the recent fabricating nano¯ber membranes. 55,56 Ou et al 57 reported for the¯rst time on the fabrication of a robust, thermo-responsive poly(N-isopropylacrylamide) (PNIPAM) hydrogel-coated PU membrane by centrifugal spinning for e®ective separation of oil/water emulsions. The reason of selecting thermoplastic PU was its high tensile strength, wear resistance and good°exibility over a wide temperature range.…”
Section: Centrifugal Spinning Methodsmentioning
confidence: 99%
“…With advantages of low cost and high e±ciency, centrifugal spinning technology has been developed from the initial preparing arti¯cial hair to the recent fabricating nano¯ber membranes. 55,56 Ou et al 57 reported for the¯rst time on the fabrication of a robust, thermo-responsive poly(N-isopropylacrylamide) (PNIPAM) hydrogel-coated PU membrane by centrifugal spinning for e®ective separation of oil/water emulsions. The reason of selecting thermoplastic PU was its high tensile strength, wear resistance and good°exibility over a wide temperature range.…”
Section: Centrifugal Spinning Methodsmentioning
confidence: 99%
“…By using this process, one could produce an efficient layer of an organic solar cell. 135 Further potential applications being studied include supercapacitors based on flexible graphene/polyaniline nanofiber composite films [136], graphene/polyaniline nanofiber composites as supercapacitor electrodes, 137 lithium-ion battery separators from PAN, 77,138 polystyrene (PS) nonwoven fabrics featuring radiation induced color changes, 139 nanofiber hydrophilic studies 70,140,141 and anionic dye adsorption techniques [142] to name but a few.…”
Section: Processing and Propertiesmentioning
confidence: 99%
“…[154] Other thermoresponsive membrane composites containing PNIPAAm have also been used to efficiently separate oil-water mixtures and even oil-in-water and W/O emulsions. [155,156] In addition, thermoresponsive melamine sponges containing PNIPAAm can effectively absorb and release oil under water with alternative high and low temperature, respectively, which has potential for smart oil/water separation. [157] …”
Section: Thermoresponsive Surfaces For Separationmentioning
confidence: 99%